Knowledge, attitudes and practice of salt intake and blood pressure level in a multi-ethnic population in Malaysia - Chew, Ming Tsuey *; Chia, Yook Chin *; Oui, Jethro Ee Keat; Ching, Siew Mooi *; Devaraj, Navin Kumar; Lim, Hooi Min; Chew, Bee Nah; Mohamad, Mohazmi; Ooi, Pei Boon *; Be, Hooi Chin (Lippincott, Williams & Wilkins, 2023)
Knowledge, attitudes and practice of salt intake and blood pressure level in a multi-ethnic population in Malaysia